Industrial policy and governments' cybersecurity capacity: a tale of two developments?. Issue 2 (4th May 2022) - Tijerina, Walid
ABSTRACT: Are industrial policies having an impact on countries' cybersecurity capacity across the globe? When analysing the securitisation of countries' cyberspace, the empirical assessment of industrial policies is still rather unexplored. In parallel, scholars in the field of development have already raised their concerns regarding the risk for developing countries falling further behind vis-à-vis developed countries as a consequence of the disruptive dynamics brought forth by new technologies. Still, empirical studies that contrast the dynamics that new technologies are posing among developed and developing countries are rather scant. This paper looks to contribute to the empirical literature by assessing the role of industrial policy in cyber-related challenges through a cross-country OLS estimation model. Results show that industrial policies are having a significant impact across countries' cyber capacities and that, moreover, there is an interactive relationship between countries' cybersecurity capacities and R&D efforts once development values are controlled.